Pengaruh Pengatahuan Wajib Pajak, Kesadaran Wajib Pajak, dan Tarif Pajak terhadap Kepatuhan Wajib Pajak Restoran - Charisma Zega Cinta Varera; Suprihati Suprihati; Darmanto Darmanto (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This research aims to examine how taxpayer knowledge, taxpayer awareness, and tax rates influence the tax compliance of restaurant taxpayers in Karanganyar Regency. The study uses a quantitative approach with data collected through structured questionnaires. A total of 85 respondents were selected using the simple random sampling method from restaurant taxpayers registered at the Regional Financial Agency of Karanganyar Regency. The results show that taxpayer knowledge and awareness both significantly affect tax compliance. In contrast, the tax rate variable does not show a significant effect. These findings indicate that the more knowledgeable and aware taxpayers are, the more likely they are to comply, regardless of the applicable tax rate.